Comment on 26 cm Fall Caught on Video Causing Subdural Hemorrhages and Extensive Retinal Hemorrhages in an 8‐Month‐Old Infant - Michelle Shouldice; Jennifer N. Smith (Clinical Case Reports, 2024)
ABSTRACT This Letter to the Editor comments on and aims to clarify details regarding the case, 26 cm fall caught on video causing subdural hemorrhages and extensive retinal hemorrhages in an 8‐month‐old infant. The findings in this case are rarely reported in accidental injury events and are, therefore, important to understand.